The economic and environmental impacts of increasing the Irish carbon tax - Kelly C. De Bruin; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2018)
This research examines the impact of an increase in the current carbon tax. This study was undertaken as part of a joint research programme with the Department of Finance and the Revenue Commissioners.
Keywords: 330